Novel Pharmacological Therapy in Inflammatory Bowel Diseases: Beyond Anti-Tumor Necrosis Factor - Pagnini, Cristiano; Pizarro, Theresa T.; Cominelli, Fabio (Frontiers in Pharmacology, 2019)
Inflammatory bowel diseases (IBD) are chronic conditions of the gastrointestinal tract in which dysregulated immune responses cause persistent inflammation of the gut mucosa. Biologic therapy with anti-TNF blockers has revolutionized the therapeutic management of IBD for their remarkable efficacy and potential impact on disease course and for many years, has represented the sole treatment option for patients refractory or intolerant to conventional therapy. In recent years, more molecules, both biologically- and chemically-synthetized, have been developed as potential therapeutic options for IBD that target different molecular pathways aside from TNF blockade, and which have been proposed as targets for novel drugs. This is particularly relevant for the present, as well as future, management of IBD, considering that some patients are refractory to anti-TNF. This review will summarize the pharmacological options, either currently available or in the pipeline, for market approval to treat IBD, besides anti-TNF strategies, based on their mechanism(s) of action. We will also analyze the current evidence for effectiveness and safety, as well as offer perspective, regarding the potential implementation for such therapies in the future.